2016
DOI: 10.4187/respcare.04516
|View full text |Cite
|
Sign up to set email alerts
|

Is Renal Impairment an Anticipated COPD Comorbidity?

Abstract: BACKGROUND: Many studies have investigated COPD-linked comorbidities and their influence on associated outcomes, but the extent to which COPD is related to chronic renal failure is undetermined. The objective of this work was to assess the prevalence of chronic renal failure (overt or concealed) in a cohort with COPD compared with that of a control group, and to investigate the relationships of the clinical and functional data with the subjects' renal conditions. METHODS: The study was performed with 136 subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…A likely explanation is the higher prevalence of renal dysfunction among patients with COPD, compared to those without COPD. 27 . .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A likely explanation is the higher prevalence of renal dysfunction among patients with COPD, compared to those without COPD. 27 . .…”
Section: Discussionmentioning
confidence: 99%
“…More surprisingly, however, was the finding that MRA use was also significantly less common in patients with COPD, despite their worse functional class. A likely explanation is the higher prevalence of renal dysfunction among patients with COPD, compared to those without COPD 27 …”
Section: Discussionmentioning
confidence: 99%
“…The subgroup analysis of COPD subjects showed a similar result, while both the two analyses did not reveal an association between spirometry data and concealed CRF reported by AbdelHalim and AboElNaga. 33 We further investigated the predictive value of ADAMTS-13 on predicting concealed CRF in COPD patients using ROC curves, and the results showed that it possessed rather a high diagnostic value ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study from Egypt by Abdelhalim and AboElNaga involving 136 COPD patients and 104 control subjects provided slightly different results [ 13 ]. The percentage for concealed and overt CRF in COPD patients was 19.85% and 6.62%, respectively, whereas in the control group, it was 1.92% and 0%, respectively.…”
Section: Reviewmentioning
confidence: 99%
“…The percentage for concealed and overt CRF in COPD patients was 19.85% and 6.62%, respectively, whereas in the control group, it was 1.92% and 0%, respectively. The study found a greater prevalence of CRF in patients with a more advanced stage of COPD (Global Initiative for Chronic Obstructive Lung Disease, or GOLD, stages C and D) [ 13 ]. Another study by Elmahallawy and Qora involving 600 patients (300 COPD and 300 control) found a higher prevalence of CRF [ 14 ].…”
Section: Reviewmentioning
confidence: 99%